Upaya Peningkatan Kesejahteraan Masyarakat melalui Pemanfaatan Bahan Alam di Randusari, Mojosongo, Surakarta: Improving Community Welfare through the Utilization of Natural Resources in Randusari, Mojosongo, Surakarta - Wahyuni, Dinar Sari Cahyaningrum; Handayani, Nestri; Rakhmawati, Rita; Nugraheni, Estu Retnaningtyas; Pribadi, Fitrawan Hernuza (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Randusari Hamlet, located in Mojosongo Village, Jebres District, Surakarta City, faces environmental and health problems due to its location close to the Putri Cempo Final Disposal Site (TPA). To address social and health issues, the Natural Product Pharmacy Research Group, Pharmacy Department, Faculty of Mathematics and Natural Sciences, Universitas Sebelas Maret, conducted educational activities on the utilization of natural materials, namely citronella (Cymbopogon nardus L.). The activity was carried out on May 4, 2025, and involved 75 participants from PKK RW 30 in Randusari Hamlet. It included preparation, presentation, leaflet distribution, demonstration of simple extraction of essential oils from citronella, and evaluation through pre- and post-tests. It led to various understandings of the applications of herbal medicine. The average increase in the pre-test and post-test study was 8.4%. It showed that the activity has successfully increased public knowledge and understanding regarding the use of herbal medicines. This activity is expected to increase the knowledge of the benefits, methods, and processing of medicinal plants into valuable products.